Borderline sebaceous neoplasm in a renal transplant patient without Muir‐Torre syndrome. (23rd November 2012) - Kaminska, Edidiong C.N.; Iyengar, Vivek; Tsoukas, Maria; Shea, Christopher R.
Abstract : Borderline sebaceous neoplasms are rare tumors that can be challenging to diagnose because of their admixture of histopathologic features. Most such tumors have been described in patients with Muir‐Torre syndrome (MTS). We report the case of an immunosuppressed, 82‐year‐old African‐American woman without MTS who developed a rapidly growing lesion on the left cheek. Histopathology revealed a borderline sebaceous neoplasm with predominant features of sebaceous adenoma and with focal features raising concern for the possibility of an evolving, well‐differentiated, low‐grade sebaceous carcinoma with a high mitotic index. In the setting of immunosuppression, borderline sebaceous neoplasms may occur outside of MTS; careful evaluation and conservative treatment are recommended in managing such tumors.